Results from a test‐and‐treat study for influenza among residents of homeless shelters in King County, WA: A stepped‐wedge cluster‐randomized trial. Issue 1 (7th January 2023) - Rogers, Julia H.; Casto, Amanda M.; Nwanne, Gift; Link, Amy C.; Martinez, Miguel A.; Nackviseth, Callista; Wolf, Caitlin R.; Hughes, James P.; Englund, Janet A.; Sugg, Nancy; Uyeki, Timothy M.; Han, Peter D.; et al.
Abstract: Background: Persons experiencing homelessness face increased risk of influenza as overcrowding in congregate shelters can facilitate influenza virus spread. Data regarding on‐site influenza testing and antiviral treatment within homeless shelters remain limited. Methods: We conducted a cluster‐randomized stepped‐wedge trial of point‐of‐care molecular influenza testing coupled with antiviral treatment with baloxavir or oseltamivir in residents of 14 homeless shelters in Seattle, WA, USA. Residents ≥3 months with cough or ≥2 acute respiratory illness (ARI) symptoms and onset <7 days were eligible. In control periods, mid‐nasal swabs were tested for influenza by reverse transcription polymerase chain reaction (RT‐PCR). The intervention period included on‐site rapid molecular influenza testing and antiviral treatment for influenza‐positives if symptom onset was <48 h. The primary endpoint was monthly influenza virus infections in the control versus intervention periods. Influenza whole genome sequencing was performed to assess transmission and antiviral resistance. Results: During 11/15/2019–4/30/2020 and 11/2/2020–4/30/2021, 1283 ARI encounters from 668 participants were observed. Influenza virus was detected in 51 (4%) specimens using RT‐PCR (A = 14; B = 37); 21 influenza virus infections were detected from 269 (8%) intervention‐eligible encounters by rapid molecular testing and received antiviral treatment. Thirty‐seven percent of ARI‐participant encounters reported symptom onset < 48 h. The intervention had no effect on influenza virus transmission (adjusted relative risk 1.73, 95% confidence interval [CI] 0.50–6.00). Of 23 influenza genomes, 86% of A(H1N1)pdm09 and 81% of B/Victoria sequences were closely related. Conclusion: Our findings suggest feasibility of influenza test‐and‐treat strategies in shelters. Additional studies would help discern an intervention effect during periods of increased influenza activity.